Estudio documental de la moneda castellana de Carlos I fabricada en los Países Bajos (1517) - Francisco Olmos, José María de (Revista General de Información y Documentación, 2003)
This item deals with the numismatic document used as a medium for political propaganda by Carlos I whose coinage was considered by his subjects as a monetary coup d’état on account of his having no right to entitle himself king but only regent or governor of the kingdoms in the name of the legitimate sovereign, his mother Juana I who had been declared unable because of her insanity.